The use of rituximab in the treatment of disimmune polyneuropathy: a description of clinical cases and a literature review - V. N. Kiselev; V. G. Potapenko (Нервно-мышечные болезни)
Dysimmune neuropathies are heterogeneous group of acquired immune-mediated diseases, accompanied by damage to the peripheral nervous system. As a standard therapy, prednisolone and intravenous immunoglobulins are used. Also encouraging efficacy is demonstrated by the use of a genetically engineered chimeric monoclonal antibody to the CD20 antigen found on the surface of normal and malignant B-cells – rituximab. Rituximab shows encouraging results. We reviewed the use of rituximab for dysimmune polyneuropathies and described our experience in administration of Lewis–Sumner syndrome and myelin-associated glycoprotein related neuropathy with rituximab.